Facilitators and Barriers for Successful Breastfeeding Among Migrant Chuukese Mothers on Guam - Kathryn M. Wood PhD, RNC-OB; Kristine Qureshi PhD, RN, FAAN, CEN, APHN-BC (SAGE Publishing, 2017)
The aim of this study was to identify factors that serve as facilitators and barriers for breastfeeding among Chuukese immigrant women living in Guam. Traditionally, Chuukese women exclusively breastfeed their babies; however, it is reported that breastfeeding decreases among these women when they migrate to Guam. Little is known about why this happens. A qualitative approach that included key informant interviews and focus groups of Chuukese women ( N  = 24) who had migrated to Guam and delivered a baby on Guam within the past 5 years was completed. The project interview or discussion guides were guided by the Theory of Reasoned Action and explored facilitators and barriers for successful breastfeeding among these Chuukese immigrant women. Among this population, key facilitators for breastfeeding included high levels of self-confidence, family support, knowledge about breastfeeding, and the existence of strong traditional Chuukese cultural values. Key barriers included experiences of cultural conflict or social change, lack of support from their local community, family and health-care staff, as well as limited self-knowledge about how to manage common breastfeeding problems. Where more facilitators were reported, breastfeeding was more often practiced, and where more barriers were reported, formula feeding was more likely. Social factors, health system policies, and proactive nursing support are important influencing factors for breastfeeding among the Chuukese immigrant population on Guam. Nursing can play key roles in policy, professional leadership and practice, and social advocacy to support breastfeeding promotion and maintenance on Guam.